Avaliação do papel da interleucina-10 endógena na infecção pela bactéria Pseudomonas aeruginosa em modelo murino - Belo, Valéria Aparecida (2018)
Pseudomonas aeruginosa is a Gram-negative bacterium, considered as a human opportunistic pathogen causing acute lethal infections being of great clinical importance. The innate immune response occurs through recognition of the pathogen leading to an inflammatory response which is beneficial for the elimination of the bacterium. However, this response must be controlled being IL-10 an immunoregulator cytokine that inhibits the overproduction of proinflammatory cytokines, and also metalloproteinases (MMPs) that are associated with physiological and pathological processes and immuneregulators. Given the importance of immunological mechanisms for a better understanding of the pathophysiology of P. aeruginosa infection, the objective of this study was to evaluate the role of endogenous murine IL-10 in infection with the virulent strain P. aeruginosa PA14. To assess the role of IL-10, was performed intratracheal infection with PA14 strain in C57BL/6 or IL-10 KO mice. Ten hours after infection, the recovery of viable bacteria, histopathological and stereological analyzes, zymography and real-time PCR were performed in mice lungs. In vivo analyzes demonstrated that IL-10 KO mice were more susceptible due to the high number of viable bacteria in lung when compared to C57BL/6 group. Histopathological and stereological analyzes showed that IL-10 KO mice had alveolar septal thickening, an intense diffuse inflammation with a high concentration of inflammatory cell infiltrate and collapsed alveoli culminating with decrease in alveolar space and lung surface when compared to control animals. The activity of MMP-9, but not MMP-2, as well as IL-6 and TNF-α expression were augmented in the lungs of infected animals, being much more evident in IL-10 KO animals when compared to the other analyzed groups. Taken together, the results of this work presents in an unprecedented way the close relationship between the control of P. aeruginosa infection by endogenous IL-10 and its control over MMP-9 activity, IL-6 and TNF-α expression and the histopathological processes of this infectious process.